Fostering Student Creativity: Through Project-Based Learning E-Module with the ClassPoint.Io Gamification - Puspita, Laila; Dwi Solviana, Meita; Nafrilla, Fina; Dwi Kesumawardani, Aryani; Oktafiani, Raicha; Kurnia Hayati, Dwi; Syahril, Sulthan; Rakhmawati, Ismi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
Creativity is an essential 21st-century skill; however, observations and interviews revealed that students’ creativity in biology learning remains low. This study aimed to analyze the development procedures, feasibility, teachers’ and students’ responses, and the effectiveness of a project-based learning e-module integrated with ClassPoint.io gamification. The study employed a Research and Development (R&D) method using the 4D model, involving two subject-matter experts, two media experts, one language expert, teachers, and 30 tenth-grade senior high school students. Validation results indicated very high feasibility (media 91%, content 91%, language 93%). Teachers’ responses reached 85%, while students’ responses were 88% (limited scale) and 91% (large scale). The t-test results showed a significant effect (0.000 < 0.05), indicating that the e-module is effective in enhancing students’ creativity. Membina Kreativitas Siswa : Melalui E-Modul Pembelajaran Berbasis Proyek dengan Gamifikasi ClassPoin.Io ABSTRAK : Kreativitas merupakan keterampilan penting abad ke-21, namun observasi dan wawancara menunjukkan kreativitas peserta didik dalam pembelajaran biologi masih rendah. Penelitian ini bertujuan menganalisis prosedur pengembangan, kelayakan, respons pendidik dan peserta didik, serta keefektifan e-modul berbasis project-based learning dengan gamifikasi ClassPoint.io. Metode yang digunakan adalah Research and Development (R&D) model 4D dengan subjek 2 ahli materi, 2 ahli media, 1 ahli bahasa, pendidik, dan 30 peserta didik kelas X SMA. Hasil validasi menunjukkan kelayakan sangat tinggi (media 91%, materi 91%, bahasa 93%). Respons pendidik mencapai 85%, respons peserta didik 88% (skala terbatas) dan 91% (skala luas). Uji t-test menunjukkan hasil signifikan (0,000 < 0,05), sehingga e-modul dinyatakan efektif meningkatkan kreativitas peserta didik.